Causes of Suicide as Perceived by Educated Adults in Ondo Metropolis, Ondo State - Soetan, Margaret Kehinde; Oyetayo, Morakinyo O. (Universitas Negeri Malang, 2025)
This study examined causes of suicide as perceived by educated adults. Description survey research design was adopted for this study. Population of the study consisted of all educated adults in Ondo metropolis, Ondo State. The sample comprised two hundred (200) educated adults randomly selected from the metropolis. Structured questionnaire was used as instrument to collect data for the study. Data collected was analysed using mean, ranking, t-test and analysis of variance (ANOVA). The findings showed causes of suicide as seeing life as meaningless, terminal illness, traumatic experience, chronic pain among others. The results revealed that there is a significant difference in the perception of causes of suicide based on gender (t = 3.448). It was found that marital status does not influence the perception of causes of suicide among educated adults while religion does (F = 4.411). It was therefore recommended that both governmental and non-governmental organization should use all avenues to sensitize people on seeing life meaningful. People with terminal illness should be given social support by different groups of people around them. Peculiarity of each gender should be identified and addressed appropriately. All religions should encourage their followers to see life as meaningful no matter what is happening around them.